The electrochemical oxidation of hydrogen at activated platinum electrodes in room temperature ionic liquids as solvents - Silvester, Debbie; Ward, K.; Aldous, L.; Hardacre, C.; Compton, R. (Elsevier, 2008)
The oxidation of hydrogen was studied at an activated platinum micro-electrode by cyclic voltammetry in the following ionic liquids: [C2mim][NTf2], [C4mim][NTf2], [N6,2,2,2][NTf2], [P14,6,6,6][NTf2], [C4mim][OTf], [C4mim][BF4], [C4mim][PF6], [C4mim][NO3], [C6mim]Cl and [C6mim][FAP] (where [Cnmim]+= 1-alkyl-3-methylimidazolium, [N6;2;2;2]+=n-hexyltriethylammonium, [P14;6;6;6]+= tris(n-hexyltetradecyl)phosphonium; [NTf2]-= bis(trifluoromethylsulfonyl)amide, [OTf]-= trifluoromethlysulfonate and [FAP]-= tris(perfluoroethyl)trifluorophosphate. Activation of the Pt electrode was necessary to obtain reliable and reproducible voltammetry. After activation of the electrode, the H2 oxidation waves were nearly electrochemically and chemically reversible in [Cnmim][NTf2] ionic liquids, chemically irreversible in [C6mim]Cl and [C4mim][NO3], and showed intermediate characteristics in OTf, [BF4]-, [PF6]-, [FAP]- and other [NTf2]- -based ionic liquids. These differences reflect the contrasting interactions of protons with the respective RTIL anions. The oxidation peaks are reported relative to the half-wave potential of the cobaltocenium/cobaltocene redox couple in all ionic liquids studied, giving an indication of the relative proton interactions of each ionic liquid. A preliminary temperature study (ca. 298–333 K) has also been carried out in some of the ionic liquids.Diffusion coefficients and solubilities of hydrogen at 298 K were obtained from potential-step chronoamperometry, and there was no relationship found between the diffusion coefficients and solvent viscosity. RTILs possessing [NTf2]- and [FAP]− anions showed the highest micro-electrodepeak currents for the oxidation in H2 saturated solutions, with [C4mim][NTf2] being the most sensitive. The large number of available RTIL anion/cation pairs allows scope for the possible electrochemical detection of hydrogen gas for use in gas sensor technology.